ANALISIS KONTRIBUSI PEMUNGUTAN PAJAK KENDARAAN BERMOTOR (PKB) TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA MAGELANG TAHUN 2018 - 2021 - Damayanti, Amanda Yulia; Afifah, Annisa Nur; Sunaningsih, Suci Nasehati (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Taxes are an obligation that is inherent in every individual who meets the requirements as a taxpayer. The government collects taxes as a separate levy in accordance with regulations and as part of the role of taxpayers in fulfilling tax obligations to support national development. The purpose of this research is to determine the extent of the contribution of Motor Vehicle Tax (PKB) in increasing the Regional Original Revenue (PAD) OF Magelang City from 2018 – 2021. The method used in this study is quantitative method using secondary data obtained from the official website of Magelang City and Central Java BPS. The results of this study show that the average target and realization of Magelang City’s PAD always increase from year to year over the last five years from 2017 – 2021. The average growth rate of motor vehicle tax in Magelang City for four yearfrom 2019 – 2022 is 12,71%, while the average contribution of motor vehicle tax over five years is 7,35%. In 2018, the contribution was 0,029% and in 2019 it was 0,089%. This research is expected to provide input for local government on the importance of collecting motor vehicle taxes to increase the Regional Original Revenue (PAD) of Magelang City.